The Mathnawi of Mawlana Jalaluddin Rumi - Nicholson, Reynold A.; Kayadibi, Saim (Euromat Printing House, 2007)
Mawlána Jaláluddín Rúmí (1207-1273), better known in the West as Rúmí, is one of the greatest spiritual teachers and mystic poets of all times. He stands out like a peak amidst high mountains looking over the vast oasis of human existence. His spiritual message has touched millions of souls and hearts over the centuries. Rúmí has combined the lore of religion, Ṣúfísm and poetry before him with rare perspicacity and eloquence. His life and the Mawlawí tradition which he established are a living testimony to the vibrancy of the spiritual message of Islam. As Rúmí says in his Introduction to his masterpiece Mathnawí, his works are nothing but a poetic commentary on the essential meaning of the Qur’an, the sacred book of Islam. In the language of the Ṣúfís, Rúmí is a perfect man (al-insán al-kámil) who has sung the most beautiful and profound songs of love, compassion and companionship.